- Thread starter
- #1

#### renyikouniao

##### Member

- Jun 1, 2013

- 41

Questionetermine 1.Lim(x->infinity)e^(-x)coshx

2.Lim(x->1)[(e^x-1)/In(x)]sinhx

For 1.=Lim(x->infinity)e^(-x)/(1/coshx) so the top and bottem both go to 0.then apply the rule. Repeat this procedure 3 times the top and bottem still both go to 0,so I am stuck.

2.Circumstance same as 1.I apply the rule 2 times and both the top and the bottem go to infinity.

2.Lim(x->1)[(e^x-1)/In(x)]sinhx

For 1.=Lim(x->infinity)e^(-x)/(1/coshx) so the top and bottem both go to 0.then apply the rule. Repeat this procedure 3 times the top and bottem still both go to 0,so I am stuck.

2.Circumstance same as 1.I apply the rule 2 times and both the top and the bottem go to infinity.

Last edited by a moderator: